Bunyi Glotal Hambat dan Faringal Desis Bahasa Arab Al-Qur’an oleh Penutur Bahasa Lampung - Ariyani, Farida; Sulaeman, Dedi (FKIP Universitas Lampung, 2024)
This article reveals how two Arabic consonant sounds: the glottal stop and the pharyngeal sis are pronounced by native speakers of the Lampung language when reciting Surah Al-Fatihah. The theory used in this research is articulatory phonetics. Using this theory, each sound is described and analyzed according to place, way of articulation and sound. Data in the form of sound recordings from speakers of the Arabic language of the Al-Qur’an and speakers of the Lampung language were transcribed using the International Phonetic Alphabet (AFI), and described based on place, method of articulation and sound. To see the visualization of the sound, researchers used tools in the form of a computer program, Praat. Using the contrastive analysis method, researchers analyzed the differences in the features of the two sounds. The results of the research show that there are 6 pronunciations of glottal consonant sounds and 6 pronunciations of pharyngeal consonant sounds in Surah Al-Fatihah. These two consonant sounds are each pronounced as a vowel sound by native Lampung speakers. This research concludes that there is a change in the sound of the Arabic language of the Koran in the pronunciation of Surah Al-Fatihah by native Lampung speakers. Artikel ini mengungkapkan bagaimana dua bunyi konsonan bahasa Arab: glotal hambat dan faringal desis dilafalkan oleh penutur jati bahasa Lampung dalam melafalkan surat al-fatihah. Adapun teori yang digunakan dalam penelitian ini adalah fonetik artikulatoris. Dengan menggunakan teori ini, masing-masing bunyi dideskripsikan dan dianalisis menurut tempat, cara artikulasi serta penyuaraannya. Data berupa rekaman bunyi dari penutur jati bahasa Arab Al-Qur’an dan penutur jati bahasa Lampung ditranskripsi dengan menggunakan Alfabet Fonetis Internasional (AFI), dan dideskripsikan berdasarkan tempat, cara artikulasi dan dan penyuaraannya. Untuk melihat visualisasi bunyinya, peneliti menggunakan alat bantu berupa program komputer, Praat. Dengan metode analisis kontrastif, peneliti menganalisis perbedaan fitur-fitur bunyi kedua tersebut. Hasil penelitian menunjukkan bahwa terdapat 6 pelafalan bunyi konsonan glotal hambat dan 6 pelafalan bunyi konsonan faringal desis dalam surat al-fatihah. Kedua bunyi konsonan ini masing-masing dilafalkan menjadi bunyi vokal oleh penutur jati bahasa Lampung. Penelitian ini menyimpulkan bahwa terdapat perubahan bunyi bahasa Arab Al-Qur’an dalam pelafalan surat al-fatihah oleh penutur jati bahasa Lampung.